2006
DOI: 10.1111/j.1365-3083.2006.01734.x
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Interleukin‐6 and Interleukin‐8 Expression Following Infection with Chlamydia trachomatis Serovar L2 in a HeLa/THP‐1 Cell Co‐culture Model

Abstract: Correspondence to: Dr M. Ravaoarinoro, Département de microbiologie médicale et infectiologie, section de microbiologie clinique, CHUM-Hôtel-Dieu, 3840 rue St-Urbain, Porte 5-206, Montréal, QC H2W 1T8, Canada. E-mail: madeleine.ravaoarinoro.chum@ssss.gouv.qc.ca AbstractChlamydia trachomatis, an intracellular obligate bacterium, remains responsible for a large spectrum of disorders that can progress to chronic diseases, resulting in severe sequelae, such as tubal infertility and blindness. These sequelae may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 37 publications
2
18
2
Order By: Relevance
“…Chlamydia trachomatis infection of monocytic THP-1 cells, it has been shown that the production of these four pro-inflammatory cytokines is reduced in response to LDD (43).Taken together, it can be deduced that LDD has general anti-inflammatory properties. Inhibition of bacteria-induced cytokine secretion by doxycycline occurred in a dose-dependent manner, within a concentration range between 5-25 µg/ml, which did not show any evidence of cytotoxicity.…”
Section: Actinomycetemcomitans Lps (42) In Other Experimental Systemmentioning
confidence: 91%
“…Chlamydia trachomatis infection of monocytic THP-1 cells, it has been shown that the production of these four pro-inflammatory cytokines is reduced in response to LDD (43).Taken together, it can be deduced that LDD has general anti-inflammatory properties. Inhibition of bacteria-induced cytokine secretion by doxycycline occurred in a dose-dependent manner, within a concentration range between 5-25 µg/ml, which did not show any evidence of cytotoxicity.…”
Section: Actinomycetemcomitans Lps (42) In Other Experimental Systemmentioning
confidence: 91%
“…5). Similarly, Mpiga et al showed that IL-8 expression was sustained but that TNF-␣ levels peaked and decreased in cultures infected with Chlamydia trachomatis (27). Control of IL-8 expression has been shown to be regulated by several signaling pathways and transcriptional regulators, including but not limited to NF-B.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, mRNA measurement of cytokine expression after C. trachomatis infection of HeLa cells, SiHa cervix squamous carcinoma cells, and HT-29 colon adenocarcinoma cells showed increased levels of IL-8, GRO␣, granulocytemacrophage CSF, IL-6, and IL-1␣ (59). A HeLa-THP-1 coculture model attempting to recapitulate the in vivo cellular cross talk also identified IL-6 and IL-8 cytokine secretion that was sustained during C. trachomatis infection with IL-1␤ transiently detected (71). IL-6 and IL-8 were also detected by using cervical and epithelial cell infection models (59).…”
Section: Immune Pathway Elucidated By In Vitro Culture Modelsmentioning
confidence: 99%